Race, sex and age disparities in echocardiography among Medicare beneficiaries in an integrated healthcare system. Issue 12 (6th October 2021) - Hyland, Patrick M; Xu, Jiaman; Shen, Changyu; Markson, Lawrence J; Manning, Warren J; Strom, Jordan B.
Abstract : Objective: To identify potential race, sex and age disparities in performance of transthoracic echocardiography (TTE) over several decades. Methods: TTE reports from five academic and community sites within a single integrated healthcare system were linked to 100% Medicare fee-for-service claims from 1 January 2005 to 31 December 2017. Multivariable Poisson regression was used to estimate adjusted rates of TTE utilisation after the index TTE according to baseline age, sex, race and comorbidities among individuals with ≥2 TTEs. Non-white race was defined as black, Asian, North American Native, Hispanic or other categories using Medicare-assigned race categories. Results: A total of 15 870 individuals (50.1% female, mean 72.2±12.7 years) underwent a total of 63 535 TTEs (range 2–55/person) over a median (IQR) follow-up time of 4.9 (2.4–8.5) years. After the index TTE, the median TTE use was 0.72 TTEs/person/year (IQR 0.43–1.33; range 0.12–26.76). TTE use was lower in older individuals (relative risk (RR) for 10-year increase in age, 0.91, 95% CI 0.89 to 0.92, p<0.001), women (RR 0.97, 95% CI 0.95 to 0.99, p<0.001) and non-white individuals (RR 0.95, 95% CI 0.93 to 0.97, p<0.001). Black women in particular had the lowest relative use of TTE (RR 0.92, 95% CI 0.88 to 0.95, p<0.001). The only clinical conditions associated with increased TTE use after multivariable adjustment were heart failure (RR 1.04, 95% CI 1.00 to 1.08, p=0.04) and chronic obstructive pulmonary disease (RR 1.05, 95% CI 1.00 to 1.10, p=0.04). Conclusions: Among Medicare beneficiaries with multiple TTEs in a single large healthcare system, the median TTE use after the index TTE was 0.72 TTEs/person/year, although this varied widely. Adjusted for comorbidities, female sex, non-white race and advancing age were associated with decreased TTE utilisation.